Hybrid positron emission tomography–magnetic resonance of the heart: current state of the art and future applications. (12th July 2018) - Nazir, Muhummad Sohaib; Ismail, Tevfik F; Reyes, Eliana; Chiribiri, Amedeo; Kaufmann, Philipp A; Plein, Sven
Abstract: Hybrid positron emission tomography–magnetic resonance (PET-MR) imaging is a novel imaging modality with emerging applications for cardiovascular disease. PET-MR aims to combine the high-spatial resolution morphological and functional assessment afforded by magnetic resonance imaging (MRI) with the ability of positron emission tomography (PET) for quantification of metabolism, perfusion, and inflammation. The fusion of these two modalities into a single imaging platform not only represents an opportunity to acquire complementary information from a single scan, but also allows motion correction for PET with reduction in ionising radiation. This article presents a brief overview of PET-MR technology followed by a review of the published literature on the clinical cardio-vascular applications of PET and MRI performed separately and with hybrid PET-MR.